Oxford handbook of occupational health - Smedley, Julia; Dick, Finlay; Sadhra, Steven S. (Oxford handbooks., 2013)
This handbook provides a comprehensive summary of the theory & practice of occupational health. It covers the main areas of occupational exposure, ill-health & injury resulting from such exposure, & the practical issues in occupational health as well as current issues such as Gulf War Syndrome, SARS, & exposure to electromagnetic fields.